2020
DOI: 10.5051/jpis.2020.50.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of implant stability measurements between a resonance frequency analysis device and a modified damping capacity analysis device: anin vitrostudy

Abstract: Purpose: A stability-measuring device that utilizes damping capacity analysis (DCA) has recently been introduced in the field of dental implantology. This study aimed to evaluate the sensitivity and reliability of this device by measuring the implant stability of ex vivo samples in comparison with a resonance frequency analysis (RFA) device. Methods: Six implant beds were prepared in porcine ribs using 3 different drilling protocols to simulate various implant stability conditions. Thirty-six pork ribs and 216… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…PTV ranged between -8 and 50, where lower values indicate better stability [ 13 ]. An IST value below 59 indicated that the miniscrew was unstable, while between 60 and 64 indicated moderate stability and above 65 indicated high stability [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PTV ranged between -8 and 50, where lower values indicate better stability [ 13 ]. An IST value below 59 indicated that the miniscrew was unstable, while between 60 and 64 indicated moderate stability and above 65 indicated high stability [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…PTV ranged between -8 and 50, where lower values indicate better stability [ 13 ]. An IST value below 59 indicated that the miniscrew was unstable, while between 60 and 64 indicated moderate stability and above 65 indicated high stability [ 13 ]. The PTV of the initial insertion and re-insertion was 2.44 ± 1.11 and 3.26 ± 0.72 for non-cortical bone, -0.84 ± 0.33 and -0.30 ± 0.75 for 30 pcf bone, -2.52 ± 0.44 and -2.18 ± 0.78 for 40 pcf bone, and -3.62 ± 0.41 and -4.12 ± 0.23 for 50 pcf bone, respectively ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering an alpha error of 0.05 and a beta error of 0.2, in a two-sided test, a minimum of 20 samples were necessary on each group to identify a statistically significant difference greater than or equal than to 2 units. Based on a recent study [14], standard deviation was assumed to be 5 and the correlation coefficient measurements was 0.9. The second device was Penguin ® (Integration Diagnostics Sweden AB, Göteborg, Sweden).…”
Section: Methodsmentioning
confidence: 99%